PENDAMPINGAN PENINGKATAN LITERASI CYBER SECURITY AWARENESS BAGI UMKM DI DIY - Priantinah, Denies; Juliani, Dian; Taman, Abdullah (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
Currently, MSMEs are still less aware of the dangers associated with digital transactions. Cybersecurity literacy for MSMEs in the Special Region of Yogyakarta (DIY) Province is conducted to protect against the increasingly complicated threat of cybercrime. The main objective of this activity is assistance and education on cybersecurity procedures in digital transactions. Cyber attack simulations and practical instructions on the use of security software, including firewalls, antivirus programs, and Virtual Private Networks (VPNs), were among the techniques used. The program participants consisted of 42 MSMEs from various backgrounds. They showed significant improvement in their knowledge of digital security. The profile of the participants and the impact of the mentoring program implementation were analyzed. While most of the participants were from the culinary industry and the majority used WhatsApp as their main business platform, the program also successfully covered MSMEs from various business sectors. Despite the difficulties in the digital era, the mentoring program helped MSME players become more aware of cybersecurity, which is crucial to maintaining the viability and competitiveness of their businesses.